Aplikasi Kombinasi Macam Pupuk Organik dan N,P,K terhadap Pertumbuhan dan Hasil Padi Hitam - Anni Yuniarti; Yuliati Machfud; Maya Damayani; Eso Solihin (Soilrens, 2018)
Black Rice is a source of carbohydrate and also a native plant of Indonesia. Black Rice contains copious amount of aleurone and endospermia that produce anthocyanin antioxidant that gave dark purple to black color characteristics. Black rice also low in sugar, contains, more fiber and vitamin E. Another advantages of the black rice, is as natural medicine or nutritious functional food ingredients that prevents degenerative diseases such as cancer. Potential yield of black rice in Indonesia is around 4–5 t ha-1. In this study, the extent of the role of various types of organic fertilizers (straw compost, cattle manure, chicken manure and sheep manure) and N, P, K fertilizers on the growth and yield of black rice were investigated. The experimental design was carried out using a Randomized Block Design (RBD) consisted of 10 treatments with triplicates. The combination of treatment consisted of straw compost, cattle manure, chicken manure, sheep manure and 0-100% recommended dosage of Nitroge, Phosphate, and Potassium (N, P, K) fertilizers. Result showed that the combination of organic fertilizers and N, P, K fertilizers had an effect on plant height, number of tillers and black rice yield (dry grain weight). The application of chicken and cattle manure fertilizers with the addition of N, P, K fertilizers (1 recommended dosage) yielded 66.50 g/tiller (8,5 ton/ha)  and 66 g/tiller(8,4 ton/ha) of dry grain weight respectively.Key word: black rice, chicken manure, cattle manure, potential yield